Bartholin's gland cysts: management with carbon-dioxide laser vaporization Cistos da glândula de Bartholin: tratamento com vaporização laser com CO2 - Ana Cristina Neves Figueiredo; Paula Elisa Folgado da Silva Ambrósio Rebelo Duarte; Tereza Paula Monteiro Gomes; Jorge Manuel Paiva Borrego; Carlos Alfredo Caseiro Marques (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2012)
PURPOSE: To evaluate the effectiveness, recurrence rate, and complications of carbon-dioxide laser vaporization in the treatment of Bartholin's gland cysts. METHODS: A retrospective study including 127 patients with symptomatic Bartholin' gland cysts submitted to carbon-dioxide laser vaporization at our institution from January 2005 to June 2011. Patients with Bartholin's gland abscesses and those suspected of having neoplasia were excluded. All procedures were performed in an outpatient setting under local anaesthesia. Clinical records were reviewed for demographic characteristics, anatomic parameters, intraoperative and postoperative complications, and follow-up data. Data were stored and analyzed in Microsoft Excel® 2007 software. A descriptive statistical analysis was performed, and its results were expressed as frequency (percentage) or mean±standard deviation. Complication, recurrence, and cure rates were calculated. RESULTS: The mean age of the patients was 37.3±9.5 years-old (range from 18 to 61 years-old). Seventy percent (n=85) of them were multiparous. The most common symptom was pain and 47.2% (n=60) of patients had a history of previous medical and/or surgical treatment for Bartholin's gland abscesses. Mean cyst size was 2.7±0.9 cm. There were three (2.4%) cases of minor intraoperative bleeding. Overall, there were 17 (13.4%) recurrences within a mean of 14.6 months (range from 1 to 56 months): ten Bartholin's gland abscesses and seven recurrent cysts requiring reintervention. The cure rate after single laser treatment was 86.6%. Among the five patients with recurrent disease that had a second laser procedure, the cure rate was 100%. CONCLUSIONS: At this institution, carbon-dioxide laser vaporization seems to be a safe and effective procedure for the treatment of Bartholin's gland cysts. OBJETIVO: Avaliar a eficácia, a taxa de recorrência e as complicações da vaporização laser com CO2 no tratamento dos cistos da glândula de Bartholin. MÉTODOS: Estudo retrospectivo com 127 pacientes que apresentavam cistos sintomáticos da glândula de Bartholin submetidas à vaporização laser CO2 na nossa instituição de janeiro de 2005 a junho de 2011. Foram excluídas todas as pacientes com abcessos da glândula de Bartholin ou com suspeita de câncer. Todos os procedimentos foram realizados em regime ambulatorial, sob anestesia local. A coleta dos dados foi feita com base na consulta do processo clínico, tendo-se procedido à análise das características demográficas, dos parâmetros anatômicos, das complicações intra e pós-operatórias e dos dados de acompanhamento. Os dados foram armazenados e analisados no software Microsoft Excel® 2007, e os resultados foram apresentados como frequência (porcentagem) ou média±desvio padrão. As taxas de complicações, recorrência e cura foram calculadas. RESULTADOS: A idade média das pacientes foi de 37,3±9,5 anos (variando entre 18 e 61 anos). Setenta por cento (n=85) delas eram multíparas. A queixa mais frequente foi dor e 47,2% (n=60) das pacientes tinham antecedentes de tratamento médico e/ou cirúrgico por abcesso da glândula de Bartholin. A dimensão média dos cistos foi de 2,7±0,9 cm. Foram verificados três (2,4%) casos de hemorragia intraoperatória ligeira e 17 (13,4%) recorrências durante um período médio de 14,6 meses (variando entre 1 e 56 meses): dez abscessos da glândula de Bartholin e sete cistos recorrentes, que precisavam de uma nova intervenção cirúrgica. A taxa de cura após um único tratamento à laser foi de 86,6%. Dentre as cinco pacientes com doença recorrente que foram submetidas a um segundo procedimento com laser, a taxa de cura foi de 100%. CONCLUSÕES: Na presente instituição, a vaporização laser com CO2 parece ser uma opção terapêutica segura e eficaz no tratamento dos cistos da glândula de Bartholin.